Deprescribing in older adults: a new concept for nurses in administering medicines and as prescribers of medicine. Issue 1 (20th December 2016) - Naughton, Corina; Hayes, Nicky
Abstract : Deprescribing is a new and emerging theme in the care of older adults living with multimorbidities including frailty. Deprescribing requires a comprehensive review of risk and benefits of a medication in the context of the quality of remaining life and patient and family priorities and preferences. Nursing to date has not engaged with this issue, yet in their roles administering medicines and prescribing medicines they are a fundamental part of the pathway in deprescribing decisions and in supporting patients to make such decisions. In administering medicines, nurses are in a position to observe the degree of difficulty or burden experienced by patients due to polypharmacy or side effects of medicines. While as prescribers for adults with multimorbidities, active review of the risk and benefits of all medicines using evidence-based instruments is part of prescribing responsibility. This article is calling for a critical examination of nurses' roles in deprescribing and in supporting patients to make informed choices about their treatment. There is a need to articulate the role of nursing in this emerging area of medicines management and contribute to a multidisciplinary discourse on deprescribing. Equally professional standards and continuous professional development for nurses as prescribers and administrators of medicines needs to reflect the complexity of an older population. A deprescribing ethos challenges nurses to actively elicit patients' experiences of medicines burden, while nurse prescribers should recognise that appropriate deprescribing is as much a part of their role as appropriate prescribing.